A new Gehyra (Gekkonidae: Reptilia) from New Guinea with unique caudal scalation - Skipwith, Phillip L.; Oliver, Paul M. (Zootaxa, 2014)
We describe a new species of gekkonid gecko in the genus Gehyra from West Papua, Indonesia. Gehyra serraticauda sp. nov. keys to Gehyra, but is distinct from all known species; most notably, it is characterised by a continuous fringe of prominent acuminate lateral scales running the length of the tail, a feature shared with none of its congeners. Its robust body, intermediate size, numerous internasals, partially divided digital scansors, and the presence of well-developed popliteal folds further distinguish it from other Papuan Gehyra. The holotype of Gehyra serraticauda sp. nov. is of uncertain provenance, with the type locality listed as Fakfak, Onin Peninsula. However, the recent observation of a potential conspecific from Kaimana, Triton Bay supports the presence of this species in the region.